(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
This article contains information about the complex political situations in the Khiva and the family history of Muhammad Rahimkhan Soni (Feruz), a great statesman, famous poet, patron of culture and art, and his descendants. Brief information about the children and grandchildren of Muhammad Rahimkhan Feruz, some of the events that happened in their lives, based on historical literature and sources, is given.